More Than Merit? Evaluating the Contribution of Non-Academic Determinants to the Influence on Teachers' Behaviour in Medical Education: A Cross-Sectional Survey of First-Year MBBS Students - Amin Wani, Izat; Kour, Manmeet; Kour Sahni, Manjote (Journal of Neonatal Surgery, 2025)
Background: Although student-teacher relationships have always been known to be governed mostly by academic performance, there are indications that non-academic factors—such as looks, conduct, socio-economic status, and interpersonal relationship—are also shaping teachers' attitudes and responses towards students. These need to be identified so that equity and professionalism of medical education can be enhanced. Objective: This study aimed to evaluate first-year MBBS students' perceptions of how non-academic factors influence teachers’ behavior towards students. Methods: A cross-sectional survey was employed among first-year MBBS students using an anonymous Google Form-based, structured questionnaire. The instrument measured students' perceptions of certain academic and non-academic attributes that can influence teachers' behavior, i.e., physical looks, communication ability, assertiveness, socioeconomic position, and relationship. Descriptive statistics and inferential analyses were used to set patterns and association. Results: Preliminary findings indicate that a significant majority of students believe that non-academic factors—specifically rapport and communication style at a personal level—have an impact on teacher behavior. Gender and appearance discrimination were also mentioned. Academic performance was still a significant predictor, but a vast majority of respondents felt that non-merit considerations stepped in at times to take over from it to decide teacher attention, feedback, or support. Out of 104 respondents, 62% were females. Of all the students, only 32% had done their schooling from a government institution. 39% reported having noticed favoritism based on appearance. 52% said students who are charismatic or sociable tend to attract more attention. While 46% of students acknowledge that a strong rapport with teachers enhances interaction and access to opportunities, 34% have felt demoralized due to differential treatment. Conclusion: The study brings to perspective the nuances of interactions between merit and non-academic influences in constructing teacher-student relations in medical education. These results validate faculty development programs that enhance fairness, openness, and professionalism for creating a merit-based learning environment that is inclusive.